Pengaruh Gaji Terhadap Kinerja Pegawai Pada Dinas Pemuda dan Olahraga Kabupaten Bandung - Awaluddiin, Ihsan (Penerbit Yayasan Daarul Huda Kruengmane, 2022)
Salary is one of the determining factors for high and low employee performance. Salary is also the main factor that is needed by someone to meet their primary, secondary and tertiary needs. The purpose of this study was to find out how the salary and performance of employees and to analyze how much influence salary had on the performance of the employees of the Youth and Sports Office Of Bandung District. The method used in this research is descriptive verification. Statistical tests used in this study are correlation, determinant test, simple regression test. Based on salary research is in the good category and employee performance is also in a very good category. From the results of the study there was an effect of salaries of positive and significant employee performance. With demikin it can be reclinished that the better the salary given is the better the performance of the employee to be achieved at the Bandung Regency Youth and Sports Office. The suggestions given are with this salary can be a trigger for the spirit of employees and also to work professionally with maximum performance results.